Art of memories : curating at the Hermitage - Lépinay, Vincent Antonin (Columbia University Press, 2019)
In Art of Memories, Vincent Antonin Lépinay documents the Hermitage's curatorial practices in an innovative consideration of the museum as a cultural laboratory. Lépinay analyzes the tensions between the museum as a space of exploration of the collections and as a culture heavily invested in self-protection from the outside world.